2016
DOI: 10.3109/08958378.2016.1171934
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of waterpipe smoking on blood pressure and heart rate: a real-life trial

Abstract: Waterpipe smoking for duration as short as 15 min has acute hemodynamic effects and significantly increases systolic BP and HR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Several studies revealed that waterpipe smoking increased the blood pressure, heart rate and eventually the risk of overall cardiovascular events [36,37]. The current study showed increased systolic blood pressure in animals that were exposed to chronic WTS, consistent with Nemmar and colleagues finding [38].…”
Section: Plos Onesupporting
confidence: 90%
“…Several studies revealed that waterpipe smoking increased the blood pressure, heart rate and eventually the risk of overall cardiovascular events [36,37]. The current study showed increased systolic blood pressure in animals that were exposed to chronic WTS, consistent with Nemmar and colleagues finding [38].…”
Section: Plos Onesupporting
confidence: 90%
“…Acute exposure to water pipe smoking is associated with a significant increase in SBP and heart rate compared with nonsmoking control subjects, 30 but long-term effects remain unclear. Current use of smokeless tobacco is associated with an increased risk of CVD events in cigarette nonsmokers.…”
Section: Smoking/tobacco Usementioning
confidence: 99%
“…Several clinical studies have reported that WPS induces an increase in systolic blood pressure. This effect has been related to the sympathomimetic effect of nicotine [22,23].…”
Section: Discussionmentioning
confidence: 99%